Differential effects of lidocaine on nerve growth factor (NGF)-evoked heat- and mechanical hyperalgesia in humans - Weinkauf, Benjamin; Obreja, Otilia; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2012)
We investigated the effects of a non-specific sodium channel blocker (lidocaine) on heat pain thresholds and mechanical impact pain at day 7 and 21 after intradermal injection of 1 μg NGF. Measurements were performed in 12 healthy male subjects prior to and 5 min after intradermal injection of 150 μl lidocaine administered at concentrations of 0.01% (∼0.4 mM) and 0.1% (∼4 mM) to both NGF and control skin sites. NGF caused a maximum reduction of heat pain thresholds at day 7 (NGF 42.6 ± 0.6 vs. 49.4 ± 0.3 °C in control skin). Lidocaine sensitized normal skin for heat pain, but reduced heat hyperalgesia after NGF at day 7 (44.3 ± 0.8 °C, lidocaine 0.1%; p < 0.005). Pain upon supra-threshold mechanical impact stimulation was increased after NGF at day 7 (VAS 29 + 5) and massively enhanced at day 21 (VAS 64 + 5, p < 0.001). Lidocaine dose-dependently attenuated mechanically-induced pain at both control and NGF-treated sites. Maximum lidocaine effects on mechanical hyperalgesia were recorded at day 21 in NGF skin (pain reduction to VAS 37 ± 4, p < 0.00001). Repetitive impact stimuli caused increasingly more pain at the NGF sites at day 21 and this pain increase was efficiently suppressed by lidocaine 0.1%. Lidocaine differentially affects NGF-induced mechanical hyperalgesia (analgesic effect) and heat sensitivity of nociceptors (sensitizing effect). These opposing responses may be attributed to block of sodium channels vs. sensitization of TRPV1. NGF-evoked extreme mechanical impact pain indicates high action potential discharge frequencies, which might be more susceptible to lidocaine block.
Gesehen am 07.05.2019